Enhancing Inmates' Knowledge through Yoga Sports Socialization at the Special Rehabilitation Institution for Children - Yahya Eko Nopiyanto; Dian Pujianto; Diah Ayu Aguspa Dita; Srikandi Luna Shofiyandra; Heppy Suheri; Ipa Sari Kardi; Rasyono Rasyono (Universitas Lambung Mangkurat, 2024)
Yoga sports socialization is a community service activity aimed at increasing knowledge about yoga among the incarcerated population at the Special Rehabilitation Institution for Children (LPKA) Class II Bengkulu. To achieve this goal, a participatory community-based research method was employed, involving identifying partner needs, defining core issues, planning implementation, conducting workshops, practice or demonstrations, discussions, and evaluation activities. Partners involved in this community service activity included 20 LPKA student inmates. The activity occurred at LPKA Class II Bengkulu in Bentiring, Muara Bangka Hulu District, Bengkulu City, Bengkulu, 38119. The workshop was held on October 10, 2023. Analysis of the activities that were conducted revealed that partners experienced an increase in knowledge about yoga. Partners enthusiastically participated in yoga exercises. Additionally, partners committed to practising yoga independently using videos produced by the service team. In conclusion, this community service activity had a positive impact on partners and was effective in enhancing their knowledge of yoga.